2018
DOI: 10.1002/lt.25286
|View full text |Cite
|
Sign up to set email alerts
|

Class II Human Leukocyte Antigen Epitope Mismatch Predicts De Novo Donor‐Specific Antibody Formation After Liver Transplantation

Abstract: Formation of de novo donor-specific antibodies (dn-DSAs) has been associated with longterm immunologic complications after liver transplantation (LT). We hypothesized that human leukocyte antigen (HLA) epitope/eplet mismatch (MM) is a marker of immunogenicity and a risk factor for dn-DSA formation. Sera from 80 LT recipients were prospectively screened for dn-DSA by a Luminex single-antigen test (One Lambda, Inc., Canoga Park, CA) at 1, 2, 3, 6, 12, 18, 24, and 36 months after LT. HLA typing of the recipients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 28 publications
(70 reference statements)
3
39
1
Order By: Relevance
“…It is unknown whether unique effector functions of IgG4 subclass DSA in the presence of higher HLA expression directly contributed to the subclinical histopathology phenotypes observed in these studies or whether a predominant IgG4 subclass serves solely as a biomarker of a prolonged smoldering humoral response. It is important to recall that higher HLA eplet mismatch loads were observed with DSA presence and strength, as previously reported,[31][32][33] and also with IgG4 subclass DSA. This is consistent with a scenario in which higher alloimmune burden drives DSA development and evolution over time to a more mature IgG4 humoral response.Our findings are consistent with other studies that have shown IgG4 DSA in recipients with chronically rejected kidney and liver allografts.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…It is unknown whether unique effector functions of IgG4 subclass DSA in the presence of higher HLA expression directly contributed to the subclinical histopathology phenotypes observed in these studies or whether a predominant IgG4 subclass serves solely as a biomarker of a prolonged smoldering humoral response. It is important to recall that higher HLA eplet mismatch loads were observed with DSA presence and strength, as previously reported,[31][32][33] and also with IgG4 subclass DSA. This is consistent with a scenario in which higher alloimmune burden drives DSA development and evolution over time to a more mature IgG4 humoral response.Our findings are consistent with other studies that have shown IgG4 DSA in recipients with chronically rejected kidney and liver allografts.…”
supporting
confidence: 76%
“…Patients with detectable class II DSA, compared to those without, had a higher median (interquartile range) total class II eplet mismatch (33 vs 26 ) and HLA-DQ alone mismatch (12 [8][9][10][11][12][13][14][15][16] vs 8 [4][5][6][7][8][9][10][11][12][13][14][15]). Similarly, total class II eplet mismatch was higher for those with MFI sum >20 000 vs ≤20 000 (40 [28-51] vs 28 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]). Among subjects with class II DSA, total class II eplet mismatch was higher for those with maximum MFI > 20 000 vs ≤20 000 (39 vs 30 [21][22][23][24][25][26][27][28][29][30]…”
Section: Incidence and Strength Of Hla Class II Dsamentioning
confidence: 99%
See 1 more Smart Citation
“…The development of post‐transplant de novo DSA can occur in the absence of pretransplant HLA sensitization and has been shown to impact long‐term allograft survival. DSA that arises post‐transplant is primarily directed toward donor HLA class II mismatches and occurs in the setting of inadequate immunosuppression and/or increased HLA class II mismatching . The incidence of de novo DSA depends upon allograft type ranging from 12% in primary kidney transplants with a median time to development of 4 years and up to 30% in lung recipients within the first year post‐transplant .…”
Section: Antibodies In Organ Transplantationmentioning
confidence: 99%
“…Considerable research has been devoted to investigating the impact of the number of eplet mismatches between donor and recipient on HLA antibody formation and graft survival. Patients who were transplanted with a higher number of mismatched eplets have a higher risk for donor-specific HLA antibody formation after transplantation (Daniels et al 2018;Duquesnoy et al 2008a;Kubal et al 2018;McCaughan et al 2018;Walton et al 2018;Wiebe et al 2013). Moreover, additional studies suggest that matching based on the number of eplets may lead to an improved graft outcome in kidney (Wiebe et al 2013), heart (Sullivan et al 2015), lung (Walton et al 2016), liver (Ekong et al 2019), and cornea transplantation (Bohringer et al 2010).…”
Section: Introductionmentioning
confidence: 99%